2014
DOI: 10.1186/cc13920
|View full text |Cite
|
Sign up to set email alerts
|

The biological effects of higher and lower positive end-expiratory pressure in pulmonary and extrapulmonary acute lung injury with intra-abdominal hypertension

Abstract: IntroductionMechanical ventilation with high positive end-expiratory pressure (PEEP) has been used in patients with acute respiratory distress syndrome (ARDS) and intra-abdominal hypertension (IAH), but the role of PEEP in minimizing lung injury remains controversial. We hypothesized that in the presence of acute lung injury (ALI) with IAH: 1) higher PEEP levels improve pulmonary morphofunction and minimize lung injury; and 2) the biological effects of higher PEEP are more effective in extrapulmonary (exp) tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 41 publications
1
14
1
Order By: Relevance
“…Furthermore, data from our laboratory have shown that the acute lung inflammation induced by i.t. instillation of LPS responds to lung recruitment manoeuvres [10][11][12] and to different mechanical ventilation settings. 13 Gene expression of amphiregulin is closely related to mechanical cell stress and is not influenced by inflammation, 14 and IL-6, CINC-1, and TNF-α were chosen because they reflect inflammation during ventilator-induced lung injury.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, data from our laboratory have shown that the acute lung inflammation induced by i.t. instillation of LPS responds to lung recruitment manoeuvres [10][11][12] and to different mechanical ventilation settings. 13 Gene expression of amphiregulin is closely related to mechanical cell stress and is not influenced by inflammation, 14 and IL-6, CINC-1, and TNF-α were chosen because they reflect inflammation during ventilator-induced lung injury.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, with the increasing understanding of pathophysiological mechanisms of ARDS, the researchers have found that different types of ARDS patients have different response to mechanical ventilation and drug intervention. At present, one universal classification is to divide the ARDS into pulmonary ARDS and extrapulmonary ARDS [24]. The main pathological mechanism of pulmonary ARDS is primary alveolar damage; and the main mechanism of extrapulmonary ARDS is the pulmonary capillary endothelial injury caused by extrapulmonary factors [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, IAH was induced by packing the four quadrants of the peritoneal cavity with saline-soaked gauze dressings and closing both layers of the abdominal cavity until an IAP of 15 mm Hg was achieved [17]. This technique has some advantages over existing models.…”
Section: Discussionmentioning
confidence: 99%